Дослідження міжнародної конкурентоспроможності українських виробників БПЛА - Горбаль, Н. І.; Карачков, В. С.; Horbal, N.; Karachkov, V. (Видавництво Львівської політехніки, 2024)
Проаналізовано особливості, сучасний стан і перспективи розвитку галузі з виробництва БПЛА в світі й Україні, зроблено акцент на вплив війни на неї. Показано, що глобальний ринок БПЛА швидко зростає і є висококонкурентним. В Україні із початком повномасштабного вторгнення попит на БПЛА зріс в десятки разів, що сприяло залученню у цю галузь значних обсягів людських та матеріальних ресурсів. Показано, що сьогодні українські виробники ще великою мірою залежать від імпортних комплектуючих, передусім китайських, що істотно впливає на їх конкурентоспроможність і підвищує ризики діяльності. Та поступово, зі збільшенням обсягів виробництва, в Україні вже зростає локалізація виробництва багатьох компонентів. В Україні вже діє близько 200 виробників дронів, й у перспективі, частина виробників зможе, поряд із військовими дронами, виготовляти й цивільні моделі, ймовірно, успішно конкуруючи на глобальному ринку.

Purpose. The global UAV market is fast-growing and highly competitive. In Ukraine, with the beginning of a full-scale invasion, the demand for UAVs increased tenfold. The purpose of the article is to analyze the peculiarities of functioning, the current state of the global and domestic drone markets, as well as the post-war prospects for the development of the UAV industry in Ukraine, in particular, the current and prospective international competitiveness of Ukrainian companies. Design/methodology/approach. The study, based on the collected data on the world and Ukrainian drone market, tested the hypothesis regarding the significant potential (due to the full-scale invasion) of Ukrainian UAV manufacturers on the world market after the end of the war. The following research methods are used: analysis, synthesis, generalization, analogy, comparison, systematization, graphical methods of data display. Findings. The features, current state and prospects for the development of the UAV industry in the world and in Ukraine are analyzed, with the main emphasis on the impact of the war on it. It is shown that the global UAV market is fast growing and highly competitive. In Ukraine, with the beginning of a full-scale invasion, the demand for UAVs increased tenfold, which led to the involvement of significant amounts of human and material resources in this industry. However, it was shown that today Ukrainian UAV manufacturers are still largely dependent on imported components, primarily Chinese, which significantly affects their competitiveness and increases the risks of activity. However, gradually, with the growth of production volumes, the localization of production of many components is already increasing in Ukraine. There are already about 200 drone manufacturers operating in Ukraine, and in the future, some of them will be able to produce civilian models in addition to military drones, probably successfully competing on the global market. Practical implications. The hypothesis regarding the significant potential (due to the full-scale invasion) of Ukrainian UAV manufacturers on the world market after the end of the war, was confirmed. Originality/value. Before the full-scale invasion in 2022, Ukraine was not a significant player in the global UAV market. Today the situation is completely different though due to the acquisition of specific experience in warfare. Therefore, the study of the current state and post-war prospects for the development of the domestic UAV industry in Ukraine, in particular the prospective international competitiveness of Ukrainian companies, is innovative and valuable today.
Analysis of the international competitiveness of Ukrainian UAV manufacturers
Keywords: дрон; безпілотник; БПЛА; FPV-дрон; конкурентоспроможність; drone; UAV; FPV drone; competitiveness; E23; F10; F23; L69; M21; N44; 339.1-621.73.06